Sweetness & lightning. 5 - Amagakure, Gido (Kodansha Comics, 2017)
"Kohei and Tsumugi have been spending peaceful days in the kitchen, but that doesn't mean there aren't any bumps in the road. Tsumugi has lots of chances to be a big girl with responsibilities, from running her first errand to wearing her first fancy dress. But when she makes some yummy mocha for a classmate whose mother is sick, it brings back painful memories. Kohei must balance protecting his daughter against letting her grow up and discover things on her own. The trials both in and out of the kitchen show that even grown-ups like Kohei and Kotori have their own lessons to learn -- and it's Tsumugi's turn to be the teacher!"--Page [4] of cover.